Student Teachers Perceptions on Enhanced Duration of Secondary Teacher Education Programmes in India - Walia, Kiran (JOURNAL OF INDIAN EDUCATION, 2008)
India has one of the largest teacher education systems with about five million teachers and more than three thousand and two hundred elementary and three thousand and five hundred secondary teacher education institutions. The duration of secondary teacher education programmes is generally of one-year. Over the years stakeholders in education have strongly voiced the need for enhancing the duration of teacher education programmes for improving its quality both in theoretical inputs and in internship. An innovative two-year secondary teacher education programme was launched in five institutions in 1999. The study presents an analysis of the feedback received from student teachers on this programme. It presents their perceptions of student teachers’ role and responsibility, interests, needs and difficulties faced by them while undergoing this course. It also gives self-assessment on their professional preparedness. The study further reveals their views on enhanced duration of secondary teacher education programme, the need for enriching school level subject content and strengthening practice teaching.